(untitled) - Lewis, Norman G. (Washinton, DC, 1998)
This book provides new information on the control of monolignal coupling and on modifying the biochemical steps in their formation and configuration. The text provides a critical assessment of recent advances in delineating the relationships and biosynthetic pathways of lignins and lignans. The discussion emphasizes lignin and lignan formation, particularly the templates for lignin assembly and the control of stereochemical coupling
Keywords: Lignin,Biochemistry